Hitab açısından Kur’an-ı Kerim’in zaman ve mekan boyutu - Coşan, Kadri Ziyaettin (My University, 2008)
İslâm inancına göre hayat, dünya ve ahiretten oluşur. Dünya, ahiret için bir hazırlık niteliğindedir. Bu sebeple insanlarının dünyada bulunmasının bir gayesi vardır. Onların bu gayeye ulaşmaları için nasıl davranmaları gerektiği, Yüce Allah tarafından vahiy denen bir iletişim aracılığıyla peygamberlere bildirmiştir. Onlar da bu bilgileri insanlara duyurmuşlardır. Kur’ân, ilk insandan son peygambere kadar devam eden vahiy sürecinin en son şeklidir. O, insanların ulaştığı en yüksek medeniyet seviyesine cevap verebilecek niteliklere sahiptir. Aynı zamanda farklı zaman, mekân ve şartlar içinde yaşayan insanların ihtiyaçlarını karşılayabilecek özellikleri de bünyesinde bulundurmaktadır. Bu ve benzeri konular üzerinde yoğunlaşan çalışmamızın giriş bölümünde, önce insanın var oluşu ve dünyada bulunuşu, sonra din ve dünya arasındaki ilişki ortaya konmuş; ardından İslâm düşüncesindeki zaman ve mekâna dair görüşler aktarılmaya çalışılmıştır. Birinci bölümde ilâhî hitabın zaman ve mekân boyutuna intikali ve bu intikalin aşamaları üzerinde durulmuş. İlahî hitabın Allah Teâlâ’dan peygambere kadar ulaşma süreci incelenmiştir. Bu çerçevede Kur’ân’ın nüzul sürecinde meleklerin işlevi, vahiy hadisesi, vahyin aşamaları ve Peygamber (s.a.v.)’in vahyi alışı göz önüne serilmiştir. İkinci bölümde Kur’ân-ı Kerîm hitabının zaman ve mekânla ilgili boyutu ele alınmış. Kur’ân’ın zaman ve mekanla ilgili kavramlara yaklaşımı incelenerek, onun muhatab olan insanı zaman ve mekan ötesine taşıması ele alınmıştır. Üçüncü bölümde ise ilâhî hitabın muhatabla buluşması araştırılmış ve vahyin indiği ortam ile muhatabların hususî özellikleri ortaya konmuştur. Ayrıca farklı bir varlık boyutu olan cinlerin Peygamber (s.a.v.) ile ilişkileri incelenmiştir. Bunun ardından vahyin zaman içinde kısım kısım inmesi üzerinde durulmuş, Kur’ân-ı Kerîm ve Hz. Peygamberin hitab sahası ele alınarak çalışma sona erdirilmiştir. HOLY QUR’AN’S DIMENSIONS OF TIME AND PLACE

According to Islamic belief, life is made up of the world and the Hereafter, the former whereof is for the preparation of the latter. Therefore, there is an aim for man’s existence in this world. In this regard, prophets have been informed by Allah the Almighty as to how they are to act so that they can attain this very purpose by means of revelations. And prophets communicated these revelations to mankind. As a matter of fact, the Holy Qur’an is the final form of the process of revelations that continued from the first man to the Seal of Prophets, who has been vested with the traits to be able to reply to the highest level of civilization mankind have reached and shall reach. Again, it possesses such qualities as shall cover the requirements of people who live in different times, places and conditions at the same time. In the introduction of this work of ours that focuses on this and similar topics, we have first elaborated upon man’s existence in this world and then the relationships between the Religion and the world; and thereafter we have related opinions in Islamic thinking as regards to time and location. The first chapter deals with transition of Divine Message to the dimensions of time and place and the stages thereof in doing which the process of the conveyance of Divine Message to the Last Prophet is studied. Within this frame, the function of angels in the course of the revelation of the Holy Qur’an, the phenomena of Revelation and the stages thereof and the receipt of Revelations by the Prophet (peace be upon him) are explained. Yet, the second chapter explicates the dimensions of the Holy Qur’an with respect to time and place, whereby the Holy Qur’an’s approach to concepts concerning time and place as well as its elevating man, the addressee thereof, beyond time and place are expounded. Finally, the third chapter sheds light upon the Divine Message’s being communicated to the addressee thereof, whereby the peculiar features of the milieu wherein the Revelation was conveyed and the addressee thereof are described. Besides, the relations of the Jinn’s, a different dimension of the creation, with the Blessed Prophet (p.b.u.h) are studied. The work ends with the study of the sending of revelations in parts in the course of time and divers aspects of the messages of the Holy Qur’an and the Blessed Prophet.
Keywords: İslam Dini; Kur’an- Kerim